New contributions to the biography of Dragić Joksimović - Dostanić, Dušan; Radojević, Mijodrag (Sociološki pregled, 2026)
Dragić Joksimović (1893–1951) was a jurist and politician, MP, and cultural activist. He is known in the professional community as the defence lawyer at the trial of General Dragoljub Mihailović. After the end of this trial, Joksimović was ostracized by the communists. After he lost his civil rights and was banned from practising law, his suffering continued with imprisonment, ending in the Sremska Mitrovica Penitentiary. Joksimović was rehabilitated by a court decision in 2008. Since 2020, the Serbian Bar Association has established the “Dragić Joksimović” Charter, with the intention of granting this recognition to strengthen trust in the professional and ethical performance of legal representation. The authors of this article, based on new sources, present newly discovered data from the biography of Dragić Joksimović, especially about his family and education in Germany, supplementing and correcting the facts used so far. Joksimović received his doctorate on the topic of agricultural chambers, which was an important topic in the Kingdom of Serbs, Croats and Slovenes at the time. In the Kingdom of Serbs, Croats and Slovenes, professional organization, especially among farmers and workers, was the subject of theoretical and political debates. The research provides a more faithful picture of Joksimović’s character and work than that previously known to the professional public. Dragić Joksimović’s life and career took place in the turbulent times of the first half of the 20th century, in the period of the political crisis in Yugoslavia between the two world wars, the arrival of the “new era” of idiocratic dictatorship and single-mindedness. Joksimović’s paradigmatic fate is a reminder of the tragedy of the transformation of Serbian society and the suffering of a large part of the domestic intelligentsia after the victory of the communist revolution.